Model Pembelajaran Tipe Complete Sentence Dalam Penguasaan Kosakata Bahasa Jerman - Andi Sofyan Nur; Misnawaty Usman; Nurming Saleh (Universitas Negeri Makassar, 2021)
Abstract. The aim of this research is to examine the effectives cooperative learning model type complete sentence in mastering German vocabulary of students XI class at SMA Negeri 14 Gowa. This research is Quasi-experimental reasearch. The data was collected by reading comprehension test and was analyzed by using t-test. Population of this research was 306 students from 9 class. Sampel was selected by using simple random sampling where XI IPA 4 class with 36 students as experimental class and XI IPA 5 class with 35 students as control class. The result showed t-count is higher that t-table (t-count4,87 > t-table 1,997) with alpha significant level 0,05. It revealed that cooperative learning model type complete sentence is effective in mastering German vocabulary of XI students at SMA 14 Gowa.